On Solve Fuzzy Boundary Value Problem - Amani E. Kadhm (Journal of Madenat Alelem University College, 2017)
The main objective of this paper is to study the pyramidal fuzzy numbers in fuzzy differential equations and introduce a new approach for solving fuzzy boundary value problems. Also, we give an example, where we compare the fuzziness of ''pyramidal'' solution to that one, which is derived by the extension principle.